Desain E-Modul Fisika Dasar Berbasis Masalah Dengan Menggunakan Flip PDF Corporate Edition - Nurmasyitah Nurmasyitah; Nur Azizah Lubis; Derlina Derlina (Jurnal Penelitian Pendidikan IPA, 2022)
This research was conducted with the aim of seeing the feasibility and practicality of problem-based e-modules using Flip PDF corporate edition. The type of research used is 'Research and'Development or R&D modeled ADDIE from analyzing, designing, developing, implementing, and evaluating. This research was only carried out until the development stage in the form of a trial, namely looking at the feasibility and practicality of the physics e-module media. Furthermore, the subject in this study is a student of the Physics education study program FKIP Samudra University. The data collection instruments and techniques used in this study are questionnaires on the feasibility and practicality of problem-based e-modules using flip PDF corporate edition. The result of the data calculation is a problem-based basic physics electronic module using flip pdf corporate edition which has been designed very feasible to be developed with an average score of 92.3%. Furthermore, the problem-based basic physics electronic module using Flip Pdf corporate edition is in accordance with student needs, and is very practical to be used in a learning or educational system with an average score of 88.2%.